2018
DOI: 10.11646/phytotaxa.351.2.2
|View full text |Cite
|
Sign up to set email alerts
|

­Phylogenetic Analysis of the Genus Pohlia (Bryophyta, Bryaceae) Using Chloroplast and Nuclear Ribosomal DNA

Abstract: The genus Pohlia Hedwig is a large moss genus that has been placed in the Bryaceae family as traditionally determined. However, a molecular phylogenetic analysis has indicated that the Pohlia genus is more closely related to genera that are traditionally classified into the Mniaceae or Mielichhoferiaceae families. In this study, we performed a molecular phylogenetic analysis using evidence from four chloroplast regions (atpB-rbcL, rps4, trnG, and trnL-trnF) and one nuclear ribosomal intragenic spacer region (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These genera were transferred to Mniaceae from family Bryaceae and Mielichhoferiaceae (Buck and Goffinet 2000;Frey and Stech 2009). And these changes were supported by studies based on molecular data (Cox et al 2014;Guerra et al 2011;Niu et al 2018). Thus, Mniaceae became the largest family of order Bryales.…”
mentioning
confidence: 82%
“…These genera were transferred to Mniaceae from family Bryaceae and Mielichhoferiaceae (Buck and Goffinet 2000;Frey and Stech 2009). And these changes were supported by studies based on molecular data (Cox et al 2014;Guerra et al 2011;Niu et al 2018). Thus, Mniaceae became the largest family of order Bryales.…”
mentioning
confidence: 82%
“… 2014 ; Niu et al. 2018 ) showed that Pohlia was more closely related to Mniaceae than to Bryaceae and supported the transfer of Pohlia to Mniaceae. Shaw ( 2009 ) noted that there were distinct morphological differences among species of Mniaceae, such as species in the genera Pohlia , Mielichhoferia , and Mnium .…”
mentioning
confidence: 96%
“…Brotherus (1903) placed Pohlia in Bryaceae based on morphological characteristics. However, the results based on chloroplast genome fragment sequences (Goffinet et al 2001;Cox et al 2014;Niu et al 2018) showed that Pohlia was more closely related to Mniaceae than to Bryaceae and supported the transfer of Pohlia to Mniaceae. Shaw (2009) noted that there were distinct morphological differences among species of Mniaceae, such as species in the genera Pohlia, Mielichhoferia, and Mnium.…”
mentioning
confidence: 96%
See 2 more Smart Citations